Defend the sacred: native American religious freedom beyond the First Amendment - McNally, Michael David (Princeton University Press, 2020)
"In 2016, thousands of people travelled to North Dakota to camp out near the Standing Rock Sioux Reservation to protest the construction of an oil pipeline that is projected to cross underneath the Missouri River a half mile upstream from the Reservation. The Standing Rock Sioux consider the pipeline a threat to the region's clean water and to the Sioux's sacred sites (such as its ancient burial grounds). The encamped protests garnered front-page headlines and international attention, and the resolve of the protesters was made clear in a red banner that flew above the camp: "Defend the Sacred". What does it mean when Native communities and their allies make such claims? What is the history of such claim-making, and why has this rhetorical and legal strategy - based on appeals to religious freedom - failed to gain much traction in American courts? As Michael McNally recounts in this book, Native Americans have repeatedly been inspired to assert claims to sacred places, practices, objects, knowledge, and ancestral remains by appealing to the discourse of religious freedom. But such claims based on alleged violations of the First Amendment "free exercise of religion" clause of the US Constitution have met with little success in US courts, largely because Native American communal traditions have been difficult to capture by the modern Western category of "religion." In light of this poor track record Native communities have gone beyond religious freedom-based legal strategies in articulating their sacred claims: in (e.g.) the technocratic language of "cultural resource" under American environmental and historic preservation law; in terms of the limited sovereignty accorded to Native tribes under federal Indian law; and (increasingly) in the political language of "indigenous rights" according to international human rights law (especially in light of the 2007 U.N. Declaration of the Rights of Indigenous Peoples). And yet the language of religious freedom, which resonates powerfully in the US, continues to be deployed, propelling some remarkably useful legislative and administrative accommodations such as the 1990 Native American Graves Protection and Reparation Act. As McNally's book shows, native communities draw on the continued rhetorical power of religious freedom language to attain legislative and regulatory victories beyond the First Amendment"--